Sestrin2 Regulates Beneficial β3-Adrenergic Receptor-Mediated Effects Observed in Inguinal White Adipose Tissue and Soleus Muscle - Min Jeong Park; Joo Won Kim; Eun Roh; Kyung Mook Choi; Sei Hyun Baik; Hwan-Jin Hwang; Hye Jin Yoo (Endocrinology and Metabolism, 2022)
Sestrin2, a well-known adenosine monophosphate-activated protein kinase (AMPK) regulator, plays a protective role against metabolic stress. The β3-adrenergic receptor (β3AR) induces fat browning and inhibits muscle atrophy in an AMPK-dependent manner. However, no prior research has examined the relationship of sestrin2 with β3AR in body composition changes. In this study, CL 316,243 (CL), a β3AR agonist, was administered to wild-type and sestrin2-knockout (KO) mice for 2 weeks, and fat and muscle tissues were harvested. CL induced AMPK phosphorylation, expression of brown-fat markers, and mitochondrial biogenesis, which resulted in the reduction of lipid droplet size in inguinal white adipose tissue (iWAT). These effects were not observed in sestrin2-KO mice. In CL-treated soleus muscle, sestrin2-KO was related to decreased myogenic gene expression and increased levels of muscle atrophy-related molecules. Our results suggest that sestrin2 is associated with beneficial β3AR-mediated changes in body composition, especially in iWAT and in the soleus.